2008
DOI: 10.1113/jphysiol.2007.146605
|View full text |Cite
|
Sign up to set email alerts
|

Muscle synergies during locomotion in the cat: a model for motor cortex control

Abstract: It is well established that the motor cortex makes an important contribution to the control of visually guided gait modifications, such as those required to step over an obstacle. However, it is less clear how the descending cortical signal interacts with the interneuronal networks in the spinal cord to ensure that precise changes in limb trajectory are appropriately incorporated into the base locomotor rhythm. Here we suggest that subpopulations of motor cortical neurones, active sequentially during the step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
128
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 33 publications
(60 reference statements)
12
128
1
2
Order By: Relevance
“…This sensory representation of whole limb position ascends spinal tracts to higher brain centers and is probably an important determinant of locomotor control of the limbs. Recent work also suggests that the increased cortical activity associated with more complex walking tasks is due to modifications made during gait (Beloozerova and Sirota, 1993a;Beloozerova and Sirota, 1993b;Beloozerova and Sirota, 1998;Drew et al, 2008). This suggests the central nervous system may use neural representations of limblevel kinematics to assemble goal-equivalent, joint-level compensatory responses that correct and stabilize normal limb function on a step-by-step basis, both before and after injury.…”
Section: Limb Kinematics May Be Guiding the Selection Of Joint Angle mentioning
confidence: 99%
See 1 more Smart Citation
“…This sensory representation of whole limb position ascends spinal tracts to higher brain centers and is probably an important determinant of locomotor control of the limbs. Recent work also suggests that the increased cortical activity associated with more complex walking tasks is due to modifications made during gait (Beloozerova and Sirota, 1993a;Beloozerova and Sirota, 1993b;Beloozerova and Sirota, 1998;Drew et al, 2008). This suggests the central nervous system may use neural representations of limblevel kinematics to assemble goal-equivalent, joint-level compensatory responses that correct and stabilize normal limb function on a step-by-step basis, both before and after injury.…”
Section: Limb Kinematics May Be Guiding the Selection Of Joint Angle mentioning
confidence: 99%
“…These limb-level control signals then descend and guide lower levels of organization that select and regulate individual joint kinematics through a more automated process. The anatomical locations of these higher-level control centers are unknown, but remain an active area of research (Drew et al, 2008;Ting, 2007;Ting and McKay, 2007). At lower levels of the locomotor system, regulation of joint kinematics to consistently satisfy higher-level commands might include a mixture of active neural processes, such as autogenic and heterogenic spinal reflex pathways, and passive biomechanical mechanisms, such as the mechanical coupling associated with biarticular muscles and interaction torques.…”
Section: Limb Kinematics May Be Guiding the Selection Of Joint Angle mentioning
confidence: 99%
“…Precise comparison between muscle synergies found pre-and post-transection at different levels of the neuraxis suggested that a majority of muscle synergies underlying natural movement in frogs is expressed by the neural circuits within the brain stem and spinal cord (Roh et al 2011a). In addition, some electrophysiological and anatomical studies have suggested that neurons in the primary motor cortex (M1) are involved in expressing muscle synergies in mammals (Drew et al 2008;Futami et al 1979;Gentner and Classen 2006;Li and Martin 2002;Shinoda et al 1976Shinoda et al , 1981Shinoda et al , 1986. We reason that the two views, derived from experiments with a lower vertebrate and mammals, respectively, could be reconciled in the sense that the "old" M1 (Rathelot and Strick 2009), sending descending fibers primarily to the spinal interneurons, generates movements by flexibly activating synergies expressed downstream, whereas the "new" M1 is involved in encoding the more diverse movements peculiar to higher primates and humans (Roh et al 2011a;Yakovenko et al 2011).…”
Section: Neural Circuitries Involved In Expressing Muscle Synergiesmentioning
confidence: 99%
“…Insular cortex also plays an important role during voluntary pelvic floor contraction compared with lower limb muscles (Schrum et al, 2011). Precuneus, parahippocampal cortex, hippocampus, and lingual gyrus have been shown to be involved in cognitive aspects of movement in space (Rosenbaum et al, 2004;Epstein, 2008;Schinazi and Epstein, 2010;Wegman and Janzen, 2011;Drew and Marigold, 2015). Based on animal studies, some of these regions appear to be critical for coordinating motor activity during complex motor tasks involving object avoidance, which may involve control of foot placement and toe muscle activity (Andujar et al, 2010).…”
Section: -130mentioning
confidence: 99%
“…In this paper, we refer to these neural centers that active muscle synergies as "synergy access points." Muscle synergies may be structured in spinal circuitry (Mussa-Ivaldi et al, 1994a;Saltiel et al, 2001;Cheung et al, 2009) and are activated by supraspinal regions, such as motor cortex (Drew et al, 2008;Overduin et al, 2014;Waters-Metenier et al, 2014). However, the brain networks that enable flexible combinations of muscle synergies to generate movements have not been identified in humans.…”
Section: Introductionmentioning
confidence: 99%